Níveis de valorização de energia metabolizável de carboidrases na dieta e seus efeitos no comportamento de suínos em fase de crescimento e terminação - Martins, Glaiton Ricardo (2023)
The objective of this study was to evaluate the effect of the addition of carbohydrase enzymes in diets of growing and finishing pigs with different levels of reduction of metabolizable energy (ME) on the behavior of pigs. In the first experiment, forty-two crossbred male pigs were used, with an average initial body weight of 25.81 (0.20) kg, in a completely randomized design, with six treatments, seven replicates and one pig per experimental unit (EU). The treatments were carried out in a 2 × 3 factorial scheme, with two classes of the enzyme a-amylase (with and without inclusion of 100 g of a-amylase/t of diet) and three levels of reduction of ME (0, 50 and 100 kcal of ME/kg of diet). In the second experiment, forty hybrid pigs (Landrace × Large White), crossbred males (Agroceres PIC × DB), with an average initial body weight of 26.0 (0.9) kg, were used in a randomized block design, with four treatments, ten replicates and one pig per EU. All experimental treatments showed an addition of xylanase with an appreciation of 40 kcal of ME/kg of diet, consisted of: reference diet (RD) without inclusion of ß-mannanase, and DR with the addition of 300 g of ß mannanase/t of feed and reduction of 30, 45 and 60 kcal of ME/kg of diet, resulting in a total energy reduction of 40 (DR40), 70 (DR70), 85 (DR85), and 100 (DR100) kcal/kg. In the experiments, the behavioral observations in the growth and finishing phases were recorded by means of closed-circuit video cameras, installed in the upper part of the housing. In the first experiment, there was an effect (P < 0.05) of interaction between enzyme (ENZ) and reduction of dietary ME (ENZ*EM) on the acts of standing, idleness, sleeping and interacting of growing pigs I, on standing, lying down, eating and interacting of growing pigs II, on the behaviors of lying down and interacting of finishing pigs I, and on the standing, eating, drinking, and sleeping of finishing pigs II. In the second experiment, it was possible to observe an effect (P < 0.05) of enzyme valorization (VE) on the idleness of growing pigs II, and on the standing, lying down, sitting, idleness and eating of pigs in the finishing phase II. Supplementation with 100 g of a-amylase/t of diet with a reduction of up to 50 kcal of ME/kg of diet increases the frequency of eating of growing pigs II. The use of 300 g of ß-mannanase and 400 g of xylanase/t of diet with a reduction of 70 and 85 kcal of ME per kg increases the percentage of feed intake of finishing II pigs.